An experimental investigation on the shear mechanism of fatigue damage in rock joints under pre-peak cyclic loading condition. (January 2018) - Liu, X.R.; Kou, M.M.; Lu, Y.M.; Liu, Y.Q.
Highlights: Pre-peak cyclic shear mechanism of rock joints is revealed. Different orders of triangular asperities in rock joints. Fatigue damage and Fatigue cracks are captured. Effects of loading rates and amplitude on cyclic shear mechanical behaviors is studied. Abstract: In this study, the shear mechanism of fatigue damage in rock joints with first-order and second-order triangular asperities under pre-peak cyclic loading conditions is investigated in laboratory. A monotonic shear test is firstly conducted to determine the shear strength in rock samples containing joints with different orders of asperities. Secondly, influence of the pre-peak cyclic loading conditions with various numbers of cycles on the shear mechanism of fatigue damage in rock joints is studied at constant normal stress. In the cyclic loading conditions, two consecutive steps, such as load-controlled and displacement-controlled, are applied in tests. The load-controlled step is used to achieve the cycles of pre-peak loading in shear tests, and the displacement-controlled step is then applied to realize the final failure of rock samples with constant rate of 0.5 mm / min . Moreover, the effects of shear loading rates, numbers of cycle and cyclic shear loading magnitude on fatigue damage, peak shear strength and residual shear strength of rock joints are researched. We found that fatigue damage occurs at the second-order asperities in the upper and lower blocks within low number of cycles, but the fatigue cracks initiated with initiation angle of 90 ° with respect to the first-order asperities in the upper and lower blocks coalesce with each other (or rock joints) within the high number of cycles. Meanwhile, the variations of peak shear strength and residual shear strength of rock joints within low number of cycles are also different from ones within the high number of cycles.